ANALYSIS OF THE AIR POLLUTION INTENSITY BY DUST EMISSIONS FROM AUTO TRANSPORT IN KRYVІY RIH CITY - Долина, Олександр; Панова, Світлана (SWorldJournal, 2025)
The levels of particulate matter concentrations with diameters PM 2.5 and PM 10 were studied on the streets of Kryvyi Rih with varying traffic intensity. A direct correlation between dust concentration and air temperature, and an inverse correlation with